Analisis Siyasah Tanfidziyyah terhadap Implementasi Peraturan Bupati Pesawaran Nomor 62 Tahun 2021 dalam Pencegahan Stunting melalui Program Gerakan Orang Tua Asuh - Syafa Kamila, Salsabilla; Frenki; Jayus, Muhammad (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to examine the role of the village government in efforts to prevent and reduce stunting through the Foster Parent Movement to Prevent Stunting in Pesawaran Regency, and analyze it from the perspective of Siyasah Tanfidziyyah. The method used in this study is qualitative with a descriptive approach. Data collection was carried out through interviews, observations, and documentation with informants from the Health Office, health centers in several sub-districts, and the community. The results of the study show that the implementation of the stunting prevention program has been carried out, but it has not run optimally. This can be seen from the involvement of the village government which is still limited and has not taken place consistently, as well as coordination between parties that has not been effective. In addition, the implementation of the program also faces various obstacles, such as limited human resources, budget limitations, and low levels of public awareness. The impact of the program on reducing stunting rates in several sub-districts has also not shown significant changes. Viewed from the perspective of Siyasah Tanfidziyyah, the implementation of the policy has not fully reflected the principles of trust, justice, and benefits. Therefore, efforts are needed to increase the role of the village government, strengthen coordination between institutions, and increase community participation so that the program can run more effectively and achieve the expected goals